Feeling nature in writing: environmental education in the EFL writing course - Lestari Setyowati; Sari Karmina; Ahmad Heki Sujiatmoko; Nova Ariani (Universitas Islam Negeri Palangka Raya, Indonesia, 2022)
Environmental degradation increases the threat to ecological disaster. Thus, environmental education is crucial for disaster mitigation. This study is intended to investigate the students